Comparative Analysis of Differentially Expressed Genes and Metabolites in Waxy Maize Inbred Lines with Distinct Twin-Shoot Phenotypes - Mengfan Qin; Guangyu Li; Kun Li; Jing Gao; Meng Li; Hao Liu; Yifeng Wang; Keke Kang; Da Zhang; Wu Li (Plants)
Polyembryonic maize, capable of producing multiple seedlings from a single kernel, holds great potential value in agricultural and industrial applications, but the seedling quality needs to be improved. In this study, seedlings of two waxy maize (Zea mays L. sinensis Kulesh) inbred lines, D35 (a polyembryonic line with twin shoots) and N6110 (single-shoot), exhibited similar relative growth rates during 1 to 5 days post-germination. UPLC-MS/MS profiling of 3- to 5-day-old seedling roots and shoots revealed that H2JA, MeSAG, and IAA-Val-Me were the common differentially accumulated metabolites (DAMs) of the 3-day-old vs. 5-day-old seedlings of D35 and N6110 in the same tissues, and MeSAG, tZ9G, cZROG, and DHZROG were identified in D35 vs. N6110 across the same tissues and the same periods. RNA-seq analyses showed various processes involved in seedling development, including DNA replication initiation, rhythmic processes, the cell cycle, secondary metabolic processes, and hormone biosynthetic regulation. The differentially expressed genes (DEGs) between D35 and N6110 were significantly enriched in organic hydroxy compound biosynthetic, alcohol biosynthetic, organic hydroxy compound metabolic, abscisic acid biosynthetic, and apocarotenoid biosynthetic processes. The KEGG-enriched pathways of DAMs and DEGs identified that AUX1, AHP, A-ARR, JAR1, SIMKK, ERF1, and GID2 might be conserved genes regulating seedling growth. The integrated analyses revealed that 98 TFs were potentially associated with multiple hormones, and 24 of them were identified to be core genes, including 11 AP2/ERFs, 4 Dofs, 2 bZIPs, 2 MADS-box genes, 2 MYBs, 1 GATA, 1 LOB, and 1 RWP-RK member. This study promotes a valuable understanding of the complex hormone interactions governing twin-shoot seedling growth and offers potential targets for improving crop establishment via seedling quality.